Histological Structure of The Optic Tectum in The Fresh Water Turtle in The Clemmys caspica caspica (Gmelin, 1774): Nahla Abid Al-Ritha and Asmaa Basheer Abid - Al-Ritha, Nahla Abid (The Iraqi Journal of Veterinary Medicine, 2012)
A histological study was conducted to examine the structure of optic tectum in Clemmys caspica caspica. The results showed that the optic tectum consist of seven strata and the third stratum consists of three substrata, as follows: The stratum zonula (SZ), the stratum opticum (SO), the stratum griseum et fibrosum superficiale (SGFS) which consist of three substrata are a, b, c, the stratum griseum centrale (SGC), the stratum album centrale (SAC), the stratum griseum periventriculare (SGP), and the stratum album periventriculare (SAP). The stratum zonula (SZ) was the thinnest stratum in the optic tectum and its main thickness was (17-19) μm, while the stratum griseum et fibrosum superficiale (SGFS) was the thickest and its main thickness was (234-243) μm.The stratum opticum (SO), which represents the second stratum called the optic fibers tract, it was found that the optic fibers enter the optic tectum through this stratum while these fibers goout from optic tectum through the (SGP) which is the sixth stratum.The stratum griseum et fibrosum superficiale (SGFS) which represents the third stratum contain a large number of stallete and piriform multipolar neurons and fusiform neurons.